Insights into the mechanism of Huanglongbing tolerance in the Australian finger lime (Citrus australasica) - Weber, Kyle C.; Mahmoud, Lamiaa M.; Stanton, Daniel; Welker, Stacy; Qiu, Wenming; Grosser, Jude W.; Levy, Amit; Dutt, Manjul (Frontiers in Plant Science, 2022)
The Australian finger lime (Citrus australasica) is tolerant to Huanglongbing (HLB; Citrus greening). This species can be utilized to develop HLB tolerant citrus cultivars through conventional breeding and biotechnological approaches. In this report, we conducted a comprehensive analysis of transcriptomic data following a non-choice infection assay to understand the CaLas tolerance mechanisms in the finger lime. After filtering 3,768 differentially expressed genes (DEGs), 2,396 were downregulated and 1,372 were upregulated in CaLas-infected finger lime compared to CaLas-infected HLB-susceptible ‘Valencia’ sweet orange. Comparative analyses revealed several DEGs belonging to cell wall, β-glucanase, proteolysis, R genes, signaling, redox state, peroxidases, glutathione-S-transferase, secondary metabolites, and pathogenesis-related (PR) proteins categories. Our results indicate that the finger lime has evolved specific redox control systems to mitigate the reactive oxygen species and modulate the plant defense response. We also identified candidate genes responsible for the production of Cys-rich secretory proteins and Pathogenesis-related 1 (PR1-like) proteins that are highly upregulated in infected finger lime relative to noninfected and infected ‘Valencia’ sweet orange. Additionally, the anatomical analysis of phloem and stem tissues in finger lime and ‘Valencia’ suggested better regeneration of phloem tissues in finger lime in response to HLB infection. Analysis of callose formation following infection revealed a significant difference in the production of callose plugs between the stem phloem of CaLas+ ‘Valencia’ sweet orange and finger lime. Understanding the mechanism of resistance will help the scientific community design strategies to protect trees from CaLas infection and assist citrus breeders in developing durable HLB tolerant citrus varieties.